Estimate of housing and population in landslide risk areas in California (USA) and coastal São Paulo (Brazil) - de Oliveira-Folharini, Saulo (2018)
The States of California and São Paulo are associated historically with natural disasters including forest fires and high precipitation, respectively. These events end up causing numerous deaths and financial and social losses. Even in the face of loss of life, and in some cases despite the lack of urban planning, populations still choose to live in places of risk, valuing them for scenic beauty or exclusivity. The aim of this study is to estimate the amount of people and housing in landslide risk areas in California and the São Paulo state coastal zone, using satellite image classification, Aster DEM and census data. The results indicate that in California, from 2000 to 2016, the urban area increased 1.83% and São Paulo increased 14.92%, indicating that occupation in the landslide risk area in California was already consolidated, and in São Paulo there was a large increase in risk because the increased population. Compared to California, São Paulo’s population and housing is a much greater landslide risk.